Optimalisasi Peran Perawat Dalam Home Care Untuk Meningkatkan Kualitas Hidup Pasien Terminal - Yenny Sima; Ridwan Ridwan; Zaenal Zaenal; Sardi Anto (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Terminal patients are a group of patients with incurable diseases who require comprehensive care focused on comfort and quality of life. Home care is an effective healthcare approach to meeting the physical, psychological, social, and spiritual needs of terminally ill patients. Nurses play a strategic role in implementing home care through the provision of palliative care, family education, and ongoing support. This Community Service activity aims to optimize the role of nurses in home care services to improve the quality of life of terminally ill patients. Implementation methods include education, training, nursing support in palliative care at home, and evaluation. The results of the activity indicate an increase in nurses' understanding of palliative care, improved therapeutic communication skills, and an improvement in the comfort and quality of life of terminally ill patients. Optimizing the role of nurses in home care is expected to provide more humane services oriented toward the needs of terminally ill patients.